CLINICAL PRESENTATION AND OUTCOMES OF PATIENTS WITH MYELODYSPLASTIC SYNDROME INTRODUCTION - Jehanzeb Ur Rehman (Hematology, Transfusion and Cell Therapy)
Objective: Myelodysplastic Syndrome (MDS) is a clonal hematopoietic disorder that is characterized by dysplasia along with anaemia, thrombocytopenia or neutropenia and a risk of progression to Acute Myeloid Leukaemia (AML). In the United States, the yearly incidence of MDS is approximately 4 per 100 000 people, notably higher among older population rising tenfold by the age of eighty (80) years. Prognostic systems, such as the revised International Prognostic Scoring System (IPSS-R), offer rationally accurate estimates of survival at the population level. The goals of treatment in individuals having lower-risk MDS includes improving quality of life and minimizing Red Blood Cells (RBCs) and platelet transfusions. Therapeutic goals in patients having Higher-Risk MDS (HR-MDS), include decreasing the risk of transformation to AML and increasing survival. Haematopoietic Cell Transplantation (HCT) has the potential to cure MDS, but less than 10% of affected people undergo this treatment. Improvements in the understanding of MDS has resulted in newer management strategies for these patients. As a result, the treatment landscape for MDS patients is changing. All these advancements are expected to improve the survival rate of patients suffering from MDS. There is limited data on presentation and outcomes of MDS patients in Low Middle Income Countries (LMICs). The Aim of our study is to assess the clinical presentation and treatment outcomes in patients with MDS in a low middle income country. Methodology: This is a single-centre retrospective cohort study with analytical design, which was approved by the hospital ethics committee (IRB-017/AFBMTC/Approval/2022). The study was conducted at the Armed Forces Bone Marrow Transplant Centre, a tertiary care facility located in Rawalpindi, Pakistan and included all consecutive patients having age > 15-years diagnosed with MDS as per revised WHO 2016 criteria from January 2019 till December 2023. The data of 128 patients was collected, followed-up and analyzed for disease and survival outcomes. Patients lost to follow up in the first 12 weeks of diagnosis or with insufficient extractable data were excluded from the study. The initial demographic and clinical information collected included age, gender, clinical presentation and laboratory parameters. Bone Marrow (BM) morphology and cytogenetics were used to establish the diagnosis of MDS. Subclassification was done using revised World Health Organization (WHO) 2016 classification of hematopoietic and lymphoid tumors. Patients were risk stratified using International Prognostic Scoring System (IPSS) and Revised-IPSS (R-IPSS) scoring as per available data. Initial treatment was stratified depending upon the aim of treatment (palliative, definitive), supportive treatments given were blood products and antibiotics. For palliative intent treatments included growth factors, immunosuppressants, lenalidomide, low dose cytarabine. For the purpose of study, definitive treatment was Hypomethylating Agents (HMA), venetoclax, intermediate/high dose cytarabine and Stem Cell Transplantation (SCT). Response to treatment was documented as per recommendations of the International Working Group (IWG) 2018 for low risk and IWG 2023 for high risk MDS. For non-transplant patients OS was defined as duration from date of diagnosis till death/last follow up and DFS as duration after being transfusion independent or complete remission till any event(death/relapse) or last follow up, while for transplant patients OS was calculated as duration from date of transplant till death/last follow up and DFS as duration from date of transplant till death, relapse or last follow up percentage and frequency was calculated for categorical variables and mean ± standard deviation or median with Interquartile Range (IQR) for the continuous variables. Survival statistics were calculated using Kaplan Meier analysis. Univariate and multivariate regression was used to document significant factors affecting survival. Results: This study evaluated the clinical outcomes of 128 patients (mean age: 52.5 ± 17.01 years; range: 16‒90) with a male-to-female ratio of 3:1. Treatment intent was categorized as palliative (81 patients, 63.3%) or definitive (47 patients, 36.7%). Patients receiving definitive treatment had a mean age of 45.85 ± 14.45 years, whereas those in the palliative group had a mean age of 56.60 ± 17.23 years (p = 0.0001). Chemotherapy regimens included Hypomethylating Agents (HMA) plus venetoclax (27.3%), Low-Dose Cytarabine (LDAC) (5.5%), LDAC plus venetoclax (1.6%), and other combinations. Among those receiving curative intent treatment, 14.8% received AZA+VEN, 10.9% received decitabine+VEN, and 5.5% underwent upfront transplant. Complete Response (CR) was achieved in 11% of definitively treated patients, while 22% showed no response. Palliative treatments included erythropoietin (30.5%), ciclosporin (7%), lenalidomide (3.9%), and supportive care (14.8%). Among palliative patients, 7% achieved hematologic improvement (NTD), while 36.7% showed no response. Seventeen patients (13.3%) underwent Hematopoietic Stem Cell Transplantation (HSCT), with 11 receiving cytoreductive therapy pre-transplant. The stem cell source was Bone Marrow Harvest (BMH) for 13 patients and BMH plus Peripheral Blood Stem Cells (PBSC) for four patients. Myeloablative Conditioning (MAC) was used in 12.5%, and Reduced-Intensity Conditioning (RIC) in 0.8%. The median CD34 dose was 2.76 × 10^6. Neutrophil engraftment occurred at a median of 13 days, while platelet engraftment averaged 21.4 ± 3.82 days. Post-transplant complications included febrile neutropenia (12.5%), mucositis (10.2%), and Graft-Versus-Host Disease (GVHD) (acute: 3.1%, chronic: 5.5%). The Overall Survival (OS) rate was 42.5% with a median survival of 440 days (95% CI 161.7‒718.2). OS varied by risk group, with very low-risk patients achieving 75% OS and very high-risk patients 0% (p = 0.01). Patients receiving MAC conditioning had a 56% OS rate (p = 0.01). Disease-Free Survival (DFS) was 22.7%, with a mean DFS of 456 days. Patients achieving Non-Transfusion Dependency (NTD) had an 80% DFS, whereas those with complete response had 50% (p < 0.001). The DFS for MAC recipients was 50%, while RIC patients had 0% (p = 0.01). Chronic GVHD was associated with improved DFS (57%) (p = 0.02). Conclusion: This study examined the clinical presentation and outcomes of MDS patients, following them until June 30, 2024, to assess Overall Survival (OS), Disease-Free Survival (DFS), and transplant-related complications, including Graft-Versus-Host Disease (GVHD). The study population had a mean age of 55.5-years, with a male-to-female ratio of 3:1, consistent with prior studies. Anemia was the most common presenting symptom (85.9%), with infections (27.3%) and bleeding (20.3%) also observed. Comparisons with existing literature revealed similar trends in demographic distribution and symptomatology. Low-risk MDS treatment included erythropoietin, thrombopoietin receptor agonists, lenalidomide, and hypomethylating agents, while high-risk patients were candidates for allogeneic Hematopoietic Stem Cell Transplantation (HSCT). Palliative treatment was given to 51.6% of patients, with 7% achieving non-transfusion dependency. In contrast, 33.6% received curative therapy, achieving an 11% Complete Response (CR) rate, aligning with reported outcomes. HSCT was performed in 17 patients, with neutrophil and platelet engraftment occurring at medians of 13 and 21 days, respectively. Acute GVHD was noted in 3.1% of patients, lower than reported rates, while chronic GVHD was seen in 5.5% of cases. OS in the study cohort was 37.5%, with DFS at 21.1%. Literature comparisons demonstrated variable survival rates depending on risk stratification and treatment modality, with OS ranging from 12.1% in high-risk MDS to 75% in low-risk patients. The study’s limitations included its geographically specific population encompassing all MDS subtypes and varied treatment approaches, with follow-up durations ranging from 6 to 54 months. Larger, more controlled studies are recommended to improve result reliability and clinical applicability.